(untitled) (Journal of the College of Basic Education, 2022)
Our historical sources on the Arabian Gulf region have until recently relied on local and Arab sources, as well as foreign ones, especially British ones, in our study of the political, economic and social aspects. The result of these benevolent efforts was the issuance of many academic studies that contained information, considered indispensable additions in the field of the history of the region and enriching its facts and various developments. It was a new source that supported the Iraqi and Arabic libraries with these valuable works.